Designing the Self-Management Space of a New Smart Learning Management System - Ouadoud, Mohammed; Rida, Nouha; Chafiq, Tarik (International Journal of Advanced Corporate Learning (iJAC), 2020)
This work is mainly based on designing an IMS-LD model for self-management space for a new LMS. Our work is first to think about the conditions for creating a real LMS between learners and teachers. we try to adapt the IMS-LD model with a self-management model based on the hybridization between four learning theories as to the basis for teaching this LMS, namely traditional pedagogy, behaviorism, cognitivism, and social constructivism. These pedagogies have already proven themselves, mainly in classroom learning situations.